2022
DOI: 10.3390/ijerph192416866
|View full text |Cite
|
Sign up to set email alerts
|

Shame-Based Experiences of Homophobic Bullying and Mental Health: The Mediating Role of Self-Compassionate Actions

Abstract: Homophobic experiences with traumatic characteristics related to shame are more frequent among sexual minority (SM) than heterosexual individuals. Concurrently, SM individuals present higher levels of psychopathology and transdiagnostic processes (e.g., shame) than heterosexual individuals. Self-compassion has been identified as a protective mechanism that counteracts the effects of shame. The current study aimed to analyse which components of self-compassion affect mental health and test the mediating role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
2
1
Order By: Relevance
“…This is inconsistent with some previous evidence on social support showing that women, both heterosexual and LGBTQI+, are generally more engaged in the community and tend to use support-seeking coping more frequently than men (Pflum et al 2015). Our findings are, however, following previous literature showing that higher social support predicts better mental health for gays and bisexual men (Henry et al 2021;Pereira and Silva 2021) and lower levels (external) shame in LGBTQI+ individuals (Seabra et al 2021). Other studies also indicated that transgender individuals who perceived family support had lower levels of psychological distress than those who perceived their family members as unsympathetic or neutral (James et al 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…This is inconsistent with some previous evidence on social support showing that women, both heterosexual and LGBTQI+, are generally more engaged in the community and tend to use support-seeking coping more frequently than men (Pflum et al 2015). Our findings are, however, following previous literature showing that higher social support predicts better mental health for gays and bisexual men (Henry et al 2021;Pereira and Silva 2021) and lower levels (external) shame in LGBTQI+ individuals (Seabra et al 2021). Other studies also indicated that transgender individuals who perceived family support had lower levels of psychological distress than those who perceived their family members as unsympathetic or neutral (James et al 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings clarify the association between the components of selfcompassion and traumatic shame experiences: compassionate actions seem to be the self-compassion component more negatively associated with shame. In fact, Seabra et al (2022) found a similar result: compassionate actions presented a higher negative association with shame when compared with compassionate engagement. Regarding the association between self-compassion and psychopathology, our results are in line with two meta-analyses in SM individuals: self-compassion showed a medium negative pooled association with psychological distress (Carvalho & Guiomar, 2022;Helminen et al, 2022).…”
Section: Discussionmentioning
confidence: 59%
“…These young victims seem to resort to shame-avoidance strategies (e.g. minimization of homophobia; McDermott et al, 2008) and shame appears to mediate the relationship between homophobic discrimination and depressive symptoms among SM adults (Seabra et al, 2021b). Shame is a self-conscious and intense emotion involving feelings of inferiority, social unattractiveness, defectiveness, and powerlessness (Tracy et al, 2007) and is associated with general psychopathology (Cândea & Szentágotai, 2013).…”
mentioning
confidence: 99%